Measuring the Digital Skills of Catalan Health Care Professionals as a Key Step Toward a Strategic Training Plan: Digital Competence Test Validation Study - Elisenda Reixach; Erik Andrés; Josuè Sallent Ribes; Montserrat Gea-Sánchez; Alícia Àvila López; Bea Cruañas; Anna González Abad; Ricard Faura; Montse Guitert; Teresa Romeu; Eulàlia Hernández-Encuentra; Sandra Bravo-Ramirez; et al. (JMIR Publications, 2022)
BackgroundDespite Catalonia being an advanced region in terms of digital health adoption, the "Forum for Professional Dialogue" identified the need to improve information and communication technology (ICT) competences as one of the present and future challenges for health care professionals (HPs). ObjectiveWe aimed to validate the digital competence test developed ad hoc for this study and to measure the digital competence level of Catalan HPs to establish their current level as the baseline for designing a strategic training plan. MethodsAn exploratory observational study was conducted based on a voluntary survey where sociodemographic, professional and digital tool knowledge, digital tool use, and training needs data were collected and based on the score obtained from a digital competence test developed ad hoc. The digital competence test consisted of 2 "real-life scenarios" with 7 and 11 questions. ResultsIn total, 803 HPs, of whom 612 (76.2%) were women, completed the survey between June 28 and July 16, 2021. Most participants self-rated their digital competence level as either intermediate (384/803, 47.8%) or basic (357/803, 44.5%). The mean score in the digital competence test was 22.6 (SD 4.3). Therefore, most participants displayed a basic level of digital competence. The internal consistency of the digital competence test was 0.66, and the discrimination index of all questions was ≥0.2 for all items except for 1 question. ConclusionsThis exploratory study highlights the need to improve the digital competence of HPs working in Catalonia, with special effort being made to provide training according to the specific needs of the different HP profiles. The results have informed the Health Plan for Catalonia 2021-2025 and lay the foundations for the development and deployment of a framework program for the digital competences of HPs. The developed digital competence test shows acceptable consistency for the objective pursued, although improvements are needed to fine-tune its accuracy.